Common and unique transcription factor requirements of human U1 and U6 snRNA genes. - Bernués, J (1993)
The human U1 and U6 genes have similar basal promoter structures. A first analysis of the factor requirements for the transcription of a human U1 gene by RNA polymerase II in vitro has been undertaken, and these requirements compared with those of human U6 gene transcription by RNA polymerase III in the same extracts. Fractions containing PSE-binding protein (PBP) are shown to be essential for transcription of both genes, and further evidence that PBP itself is required for U1 as well as U6 transcription is presented. On the other hand, the two genes have distinct requirements for TATA-binding protein (TBP). On the basis of chromatographic and functional properties, the TBP, or TBP complex, required for U1 transcription appears to differ from previously described complexes required for RNA polymerase I, II or III transcription. The different TBP requirements of the U1 and U6 promoters are reflected by specific association with either TFIIB or TFIIIB respectively, thus providing a basis for differential RNA polymerase selection.